2019
DOI: 10.1016/j.intmar.2019.01.001
|View full text |Cite|
|
Sign up to set email alerts
|

Emotions within Online Reviews and their Influence on Product Attitudes in Austria, USA and Thailand

Abstract: Online reviews are of considerable interest to both practitioners and academics. Prior research has focused mostly on the valence and volume of online reviews. Questions on how the emotional content of online reviews influence consumers remain open. Given that non-verbal cues of communication are limited in the online environment, content can be a strong driver of attitudes and, in turn, online purchases. Importantly also, a wide stream of research indicates that different self-construal levels (i.e. independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 114 publications
2
33
0
1
Order By: Relevance
“…Previous studies on consumer behavior have aimed to explain the role of emotions during the decision-making process (Hennig-Thurau et al, 2006;Felbermayr and Nanopoulos, 2016;Zablocki et al, 2019). Using traditional behavioral measures, researchers have concluded that emotions, whether positive or negative, can be contagious by observing other people's experiences (Cowley, 2014;Kramer et al, 2014).…”
Section: Emotional Contagion In Behavioral Reactionsmentioning
confidence: 99%
“…Previous studies on consumer behavior have aimed to explain the role of emotions during the decision-making process (Hennig-Thurau et al, 2006;Felbermayr and Nanopoulos, 2016;Zablocki et al, 2019). Using traditional behavioral measures, researchers have concluded that emotions, whether positive or negative, can be contagious by observing other people's experiences (Cowley, 2014;Kramer et al, 2014).…”
Section: Emotional Contagion In Behavioral Reactionsmentioning
confidence: 99%
“…Actions are more from a logical perspective, whereas reactions are more from an emotional viewpoint. Positive and negative valence has been observed in online reviews, where valence indicates the evaluative direction of review (Zablocki et al, 2019) and can be positive, negative or neutral (Purnawirawan et al, 2012). Earlier research on electronic word of mouth suggests that negative valence provides data that show products negatively and positive valence provides data that show products positively.…”
Section: Literature Review and Hypothesis Formulationmentioning
confidence: 99%
“…Emotions play a major role in customers' decisions (Zablocki et al, 2019). Emotions are more in persuasive advertisements (Lau-Gesk & Meyers-Levy, 2009), and the feeling developed towards the advertisement is the feeling towards the brand (Orth & Holancova, 2003;Ullal et al, 2020).…”
Section: Literature Review and Hypothesis Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another stream of research has explored the moderating role of product and consumer-related characteristics in the effect of online reviews, including product involvement and reviewer self-disclosure (Zhu & Zhang, 2010). In the advertising field, most studies have focused on exploring the effect of online reviews and their influence on product attitudes (Zablocki et al, 2019) and brand awareness (Zhao et al, 2015). Other research has investigated factors that influence online review readers' evaluation of review helpfulness, for instance, the rating of a product based on the sentiment score of a review (F. Wang & Karimi, 2019) or on the linguistic category features of the text (Krishnamoorthy, 2015).…”
Section: Ewommentioning
confidence: 99%